Gambaran Excessive Daytime Sleepiness pada Mahasiswi Keperawatan dengan Premenstrual Syndrome - Afifah Nur Layla; Raini Diah Susanti; Iceu Amira DA (Malahayati Nursing Journal, 2026)
ABSTRACT Excessive Daytime Sleepiness impairs cognitive and academic performance. Nursing students face elevated risk due to high academic demands and biological factors such as Premenstrual Syndrome. Descriptive evidence on EDS across PMS severity levels in this population remains limited.This study aimed to describe Excessive Daytime Sleepiness among nursing students experiencing Premenstrual Syndrome.A descriptive cross-sectional study included 296 female nursing students. PMS severity was assessed using the Shortened Premenstrual Assessment Form (sPAF), and EDS was measured using the Epworth Sleepiness Scale (ESS). Data were analyzed descriptively. Most respondents had mild PMS (65.2%) and mild EDS (55.1%). A gradient pattern emerged, with a higher proportion and severity of EDS among those with moderate compared to mild PMS. All students with severe PMS (n = 2) experienced EDS, although this finding should be interpreted cautiously due to the small sample size. Affective symptoms were the most common PMS complaints, and sleepiness occurred most often in passive situations. Excessive Daytime Sleepiness is prevalent among nursing students with Premenstrual Syndrome and shows a tendency to increase with greater PMS severity, reflecting the combined impact of premenstrual biological changes and academic demands in nursing education. Keywords: Excessive Daytime Sleepiness, Premenstrual Syndrome, Nursing Students.  ABSTRAK Excessive Daytime Sleepiness merupakan kondisi kantuk berlebih di siang hari yang dapat mengganggu fungsi kognitif dan performa akademik. Mahasiswi keperawatan merupakan kelompok yang berisiko tinggi mengalami EDS akibat tuntutan akademik yang intens serta faktor biologis seperti Premenstrual Syndrome. Namun, bukti deskriptif mengenai EDS menurut tingkat keparahan PMS pada populasi ini masih terbatas.Penelitian ini bertujuan untuk menggambarkan Excessive Daytime Sleepiness pada mahasiswi keperawatan yang mengalami Premenstrual Syndrome.Penelitian ini menggunakan desain deskriptif dengan pendekatan cross-sectional pada 296 mahasiswi keperawatan. PMS diukur menggunakan Shortened Premenstrual Assessment Form (sPAF), sedangkan EDS diukur menggunakan Epworth Sleepiness Scale (ESS). Analisis data dilakukan secara deskriptif.Sebagian besar responden mengalami PMS ringan (65,2%) dan EDS ringan (55,1%). Teridentifikasi pola gradien, di mana proporsi dan derajat EDS lebih tinggi pada kelompok PMS sedang dibandingkan PMS ringan. Seluruh responden dengan PMS berat (n = 2) mengalami EDS, namun temuan ini perlu diinterpretasikan secara hati-hati. Gejala afektif merupakan keluhan PMS yang paling dominan, dan kantuk di siang hari paling sering muncul pada situasi pasif. Excessive Daytime Sleepiness umum ditemukan pada mahasiswi keperawatan dengan Premenstrual Syndrome dan cenderung meningkat sesuai keparahan PMS. Temuan ini mencerminkan interaksi antara perubahan biologis pramenstruasi dan tuntutan akademik dalam pendidikan keperawatan. Kata Kunci: Excessive Daytime Sleepiness, Premenstrual Syndrome, Mahasiswi Keperawatan.